A invenção de Hilda Hilst para narrar e consumir: fazer-memória nos fluxos midiáticos - Bacega , Débora Regina (2024)
This research articulates the interfaces of memory, communication and consumption, and has as its theme bio-bibliographical collections understood as sociocultural phenomena. These collections, as long as they are in the media flow, constitute the theoretical object. In turn, the bio-bibliographical collections of writer Hilda Hilst (1930-2004) are the empirical object. A series of communicational, editorial and aesthetic initiatives related to its collections is identified, materialized in photographs, artistic practices, in addition to its creation space, Casa do Sol. From these collections, its interrelationships in friendships or artistic partnerships are observed. Thus, the goal is to problematize the understanding of how this genealogy articulates the writer's memory-making in new layers of bio-bibliographical collections in media flow. It is understood, as a hypothesis, that this genealogy activates and produces new layers of Hilstian biobibliographical collections in cultural and media memory. The objective is to build and analyze Hilda Hilst's genealogy. For this purpose, the theoretical framework includes the theory of the Tartu-Moscow Semiotics School in the view of Iúri Lotman and Boris Uspênski and their commentators Jerusa Ferreira, Mônica Nunes and Irene Machado, as well as key authors on the themes of archive and memory: Fausto Colombo, Paul Ricoeur, Aleida Assmann, Régine Robin, Arlette Farge and Mary Carruthers. The studies of Tim Ingold, Siegfried Zielinski, Siegfried Kracauer, Ruth Rosengarten and Hans Obrist are used in this investigation. The sociocultural, symbolic and media theory of consumption is also used. In this sense, a theoretical-methodological proposal is created for this qualitative research, with four artifacts: Tarrafa of hashtags, the Micrography of cultural tissues, the Phloem sap of companion cells and the Bioencruzilhada of mnemonic narratives. Complementary bibliographic and documentary research is adopted in this investigation. It is expected to demonstrate how Hilda Hilst's genealogy triggers the memory-making of the poet and her companion cells, sometimes in a semiotic continuum, sometimes in Lotmanian explosive processes, boosting the invention of a bioencruzilhada of mnemonic narratives, due to new layers of collections in media flow. Therefore, the genealogy of Bioencruzilhadas, adopted in this thesis about Hilda Hilst, can be expanded to the collections of other cultural personalities.